2022
DOI: 10.1007/s40368-022-00741-7
|View full text |Cite
|
Sign up to set email alerts
|

Oral health-related quality of life in portuguese pre-school children: a cross-sectional study

Abstract: Purpose To study Oral Health related Quality of Life (OHRQoL) of pre-school children and its associated factors. Methods Cross-sectional study with sample data collected through an on-line questionnaire to a non-probabilistic sample. The questionnaire included the Portuguese version of the Early Childhood Oral Health Impact Scale (ECOHIS) and questions about sociodemographic characteristics, oral health behaviours, and reported oral health of the child. Data analyses included descriptive statistics, Mann-Whitn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
0
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 19 publications
1
0
0
1
Order By: Relevance
“…In this study, the mean ECOHIS Total score was 2.21 (SD=4.09), which can be considered low. Validation studies carried out in Colombia ( 25 ) and India ( 26 ) showed similar results, which is in line with other studies carried out in Portuguese populations ( 50 , 51 ). Other ECOHIS validation studies showed higher means ( 22 - 24 , 27 , 31 , 35 ), with a wide range of values between 3.7 ( 22 ) and 25.7 ( 27 ) .…”
Section: Discussionsupporting
confidence: 89%
“…In this study, the mean ECOHIS Total score was 2.21 (SD=4.09), which can be considered low. Validation studies carried out in Colombia ( 25 ) and India ( 26 ) showed similar results, which is in line with other studies carried out in Portuguese populations ( 50 , 51 ). Other ECOHIS validation studies showed higher means ( 22 - 24 , 27 , 31 , 35 ), with a wide range of values between 3.7 ( 22 ) and 25.7 ( 27 ) .…”
Section: Discussionsupporting
confidence: 89%
“…In addition, the low frequency of tooth brushing can be contributed to the low SES in the current study. In contrary, a higher frequency of tooth brushing was seen in Freire and colleagues' study due to parental supervision and guidance during teeth brushing [14].…”
Section: Discussioncontrasting
confidence: 61%
“…Os problemas relacionados com a saúde oral têm demonstrado ter um impacto negativo nas atividades quotidianas, provocando dor, sofrimento, constrangimentos psicológicos e privações sociais, podendo desta forma influenciar negativamente a qualidade de vida dos indivíduos. 12,17,18 Pretendeu-se com o presente trabalho contribuir para o conhecimento desta temática.…”
Section: Discussionunclassified